Notary Liability That Does not Pay Bea Acquisition of Land And Building For Application Process Rights to Building - Akta Kusuma Wijaya Jati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2018)
Purpose of this paper is to determine whether the Notary authorized to make the deed of release and granting of land rights and whether Notary authorized to receive money deposits that are deposited from client BPHTB. The conclusions are as follows: Notaries have the authority to make the deed land rights, the release of land rights held, whereas subjects that require land does not qualify to be the holder of the rights to the land necessary so it can not be obtained with the purchase and land-rights holders are willing to relinquish their land rights. PT. Pawnshops do not qualify as holders of land titles it releases, so the release was not carried out in the presence of PPAT, but in the presence of a notary as public officials who have the authority a deed covenant (covenant waiver of land on ownership status). Notary authorized to receive money deposit BPHTB deposited from client, given notary as a public official in increasing source of state revenues from taxes, notary also plays a major role because they are assigned to investigate had paid income tax (VAT) of revenue as a result of transfer of rights over land and Customs Acquisition land and Building before a deed, this means that if client are not paying taxes to the Tax Administration, client can leave a notary public also plays a major role because they are assigned to investigate had paid taxes due to the transfer of rights over land and Customs Acquisition rights to land and Building.